Research on NS2-based optical burst switching network simulation platform - ZHU Zhi-jun1; LE Zi-chun2; ZHU Ran1 (Tongxin xuebao)
An OBS network simulation platform OBS-NP（OBS-NS2-platform） based on NS-2 was presented.It extended the node class and link class on the basis of NS-2, and provideed the simulation surroundings for key optical burst switching algorithms.After detailed description for the structure of the OBS-NP system, a OBS network with nine nodes was taken as an example to obtain routing results and some significant network parameters, such as the throughput, delay of the burst packets and resource utilization.Finally, the accuracy of the simulation results was discussed and analyzed.